2019
DOI: 10.1002/jemt.23209
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ultrasonic activation on dentinal tubule penetration of calcium silicate‐based cements

Abstract: This study investigated the dentinal tubule penetration of mineral trioxide aggregate (MTA), NeoMTA Plus and Biodentine placed by either manual condensation or ultrasonic activation in simulated open apex model. Standardized divergent open apex models were created using palatal roots of 60 human maxillary molars and divided into six groups according to the used cements and activation methods (n = 10): MTA‐manual condensation, MTA‐ultrasonic activation, NeoMTA Plus‐manual condensation, NeoMTA Plus‐ultrasonic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Dentinal tubule penetration of materials might be observed with microscopes such as stereomicroscope, scanning electron microscopy (SEM) and CLSM. Earlier studies suggested CLSM as it provides 3D analysis and quantitative evaluation and does not require special sample preparation before scanning, unlike the SEM technique (13,14). In CLSM analysis, irrigation solution or sealer is mixed with rhodamine-B fluorescent dye for visualisation of material penetration into dentinal tubules and the samples are horizontally sectioned.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dentinal tubule penetration of materials might be observed with microscopes such as stereomicroscope, scanning electron microscopy (SEM) and CLSM. Earlier studies suggested CLSM as it provides 3D analysis and quantitative evaluation and does not require special sample preparation before scanning, unlike the SEM technique (13,14). In CLSM analysis, irrigation solution or sealer is mixed with rhodamine-B fluorescent dye for visualisation of material penetration into dentinal tubules and the samples are horizontally sectioned.…”
Section: Discussionmentioning
confidence: 99%
“…Dentinal tubule penetration of sealer may be affected by the physical properties of endodontic sealers such as setting time, flow and film thickness (13). Camilleri (28) reported that the properties of sealers were adversely changed by heat.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasonic agitation of endodontic sealer before insertion of the gutta-percha cone has been proposed as a resource to optimize the filling of root canals with anatomical complexities 17 , 18 . On the other hand, it has also been reported that ultrasonic agitation does not improve the penetration of bioceramic materials into intratubular dentin 19 , 20 . To date, there is no data in the literature on the effect of ultrasonic agitation on the filling capacity of ready-to-use calcium silicate-based sealer or in powder-liquid presentation.…”
Section: Introductionmentioning
confidence: 98%
“…The potential of the root-end filling materials to adhere to the surrounding dental tissue is desirable to provide sealing and avoid bacterial leakage and contamination [ 5 ]. Therefore, it is important to evaluate the interactions between teeth and materials in dentistry, since gaps between the dentin and material could promote poor sealing [ 6 7 ]. The selection of an appropriate material is a challenge in clinical practice, mainly because there is little information about the adaptation of materials to dentin [ 8 ], which is critical for achieving favorable treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%